1980
DOI: 10.1002/chin.198033079
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PREPARATION, CRYSTAL STRUCTURE, AND MAGNETIC PROPERTIES OF BIS(1,2‐BENZOQUINONEDIIMIDE)‐1,2‐BENZOSEMIQUINONEDIIMIDECOBALT(II) TETRAPHENYLBORATE PENTAHYDRATE

Abstract: Ausgehend von Tris‐[1,2‐diaminobenzol]‐cobalt(II)‐perchlorat kann man durch sehr vorsichtige Oxygenierung in ethanolischer Lösung zwei verschiedene Intermediärkomplexe isolieren, bei denen es sich um einen high‐spin und einen low‐spin‐Co(II)‐ Komplex mit einem Radikalliganden handelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The difference could be caused by the stability of the photodehydrogenated form of each complex. In the case of 3d late-transition-metal complexes (number of d electrons !7), the strong ligand field of s-bqdi or bqdi in the photodehydrogenated intermediates could lead to the drastic structural change and the ligand dissociation as in the air-oxidation of [Co (opda) 3 ] 2+ [34], although the stable oxidized form, [Fe(bqdi) 3 ] 2+ can be formed easily by the oxidation of [Fe(opda) 3 ] 2+ (Scheme S2). In addition to such difference in the stability of the intermediates, their reactivities toward HQ might also cause the difference in the catalytic HER activities.…”
Section: Photochemical Hersmentioning
confidence: 97%
See 1 more Smart Citation
“…The difference could be caused by the stability of the photodehydrogenated form of each complex. In the case of 3d late-transition-metal complexes (number of d electrons !7), the strong ligand field of s-bqdi or bqdi in the photodehydrogenated intermediates could lead to the drastic structural change and the ligand dissociation as in the air-oxidation of [Co (opda) 3 ] 2+ [34], although the stable oxidized form, [Fe(bqdi) 3 ] 2+ can be formed easily by the oxidation of [Fe(opda) 3 ] 2+ (Scheme S2). In addition to such difference in the stability of the intermediates, their reactivities toward HQ might also cause the difference in the catalytic HER activities.…”
Section: Photochemical Hersmentioning
confidence: 97%
“…Herein, the synthesis, structural characterization, and photo induced HERs of a series of 3d transition-metal complexes bearing opda ligands, [M(opda) 3 ](ClO 4 ) 2 ([M-opda], M = Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Zn 2+ ), are reported. Although these opda complexes were reported previously [33][34][35], they were discussed mainly from the viewpoint of metal-centered spectroscopic properties (e.g., dÀ Àd transitions) and photochemical reactions have not been investigated. We found that these 3d metal complexes have the photochemical hydrogen production abilities.…”
Section: Introductionmentioning
confidence: 97%